Contextual Redefinition Strategy for Management Students - Pratiwi, Berlin Insan; Rakhmasari, Dwi Lia (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2019)
As Contextual Redefinition (CR) provides chances to guess meaning of word by its surrounding, it is expected to encourage students to participate more by contributing in the required steps. This study aims to measure implementation effects (score and class involvement) of CR toward Management study programme students and to find out their attitude of it. Conducted as an experimental research, this research involves three cycles of treatment. It is fulfilled with description of students attitude toward CR implementation in which the data is gained through questionnaire. Three findings are as follow: 1) CR provides mean score betterment of 61.58 on pretest to 69.11 on post-test with the absence of saturation until the end of cycle three; 2) CR activates students with class involvement increase of 16.19 on each cycle; and 3) CR is favoured by 47.54% students and 55.88% students expecting CR to be applied in every reading section. The findings indicate that despite having good significance in improving the score, this strategy is favored by less than half of students and only half and so will require its application in the process of class lecturing.